2021
DOI: 10.1002/aenm.202101424
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Cu Nanoparticle Surface Oxidation States Tunes Catalytic Selectivity toward CH4 or C2+ Products in CO2 Electroreduction

Abstract: Herein, a facile seed‐assisted strategy for preparing Cu nanoparticles (NPs) with polyvinyl pyrrolidone (PVP) capping is presented. Compared to the Cu NPs with deficient PVP protection, the Cu NPs capped with a sufficient amount of PVP remain almost completely as Cu0 species. In contrast, the Cu NPs that are considered PVP deficient form an oxide structure in which the inner layer is face‐centered cubic Cu and the outer layer is, at least in part, made up of Cu2O species. Furthermore, to eliminate CO2 molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 62 publications
0
63
0
Order By: Relevance
“…DFT results showed that the coexistence of Cu + and Cu 0 on the catalyst surface is beneficial for C-C coupling. 107,108 Therefore, increasing the Cu + content and stability in Cu catalysts has been developed as an important strategy to enhance their C 2+ selectivity.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“…DFT results showed that the coexistence of Cu + and Cu 0 on the catalyst surface is beneficial for C-C coupling. 107,108 Therefore, increasing the Cu + content and stability in Cu catalysts has been developed as an important strategy to enhance their C 2+ selectivity.…”
Section: Adsorption Strength Regulationmentioning
confidence: 99%
“… 2 Cu-based electrocatalyst studies indicated that CO 2 reduction inclines to multicarbon products (C 2 + ) on Cu + sites. 20 , 21 This progress reveals distinct impacts of the Cu valence in semiconductor materials on the photoreaction products.…”
Section: Introductionmentioning
confidence: 89%
“…[12][13][14][15][16] Moreover, regulating the valence state of copper or optimizing the distribution of multi-valent copper in CuO x catalysts has been reported to enhance the overall CO 2 RR performance. [17][18][19][20][21][22][23] Specifically, based on density functional theory (DFT) calculations, Goddard et al suggested that the interfaces between Cu + and Cu 0 regions could promote C 2 + production. [24] Wu et al reported that Cu surfaces with coexistent Cu 0 and Cu + surprisingly alter the CO 2 reduction mechanism and improve the C 2 product selectivity in the CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%